The Calculation of Economic Heat Protection and Energy Efficiency of the System of External and Internal Protections in Stock and Poultry Buildings - Ergashev, Shakhriyor Khamudillaevich (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses ways to improve the technical and economic efficiency of the use of the heliobiological heating system, including the use of rational heat occupied local materials with a thickness of 0.025, 0.0.35, 0.05 m of external and internal fences to ensure optimal energy efficiency in stock and poultry buildings.